Abandoned pastures and restored savannas have distinct patterns of plant–soil feedback and nutrient cycling compared with native Brazilian savannas. Issue 7 (17th May 2022) - D'Angioli, André M.; Giles, André L.; Costa, Patricia B.; Wolfsdorf, Gabriel; Pecoral, Luisa L. F.; Verona, Larissa; Piccolo, Fernanda; Sampaio, Alexandre B.; Schmidt, Isabel B.; Rowland, Lucy; Lambers, Hans; Kandeler, Ellen; et al.
Abstract: Around 40% of the original Brazilian savanna territory is occupied by pastures dominated by fast‐growing exotic C4 grasses, which impact ecosystem nutrient cycling. The restoration of these areas depends on the re‐establishment of soil processes. We assessed how restoration of abandoned pastures through direct seeding of native species and land‐management practices (burning and ploughing) affect soil nutrient cycling dynamics compared with native savannas. We compared the activity of soil enzymes related to carbon, nitrogen (N) and phosphorus (P) cycling as well as soil microbial biomass and soil chemical properties (pH and the concentration of N, P, potassium [K] and soil organic matter) among abandoned pastures, native savanna and restored areas. Abandoned pastures had faster nutrient turnover than native savanna, dominated by slow‐growing native species. This pattern was evident from the overall higher biomass‐specific enzyme activities in abandoned pastures than in native savanna. Compared with native savanna, restored areas had similar levels of soil enzyme activities, but lower microbial biomass and soil organic matter. The low enzyme activity in restored areas was likely related to a reduced soil organic carbon concentration due to practices such as burning and ploughing, rather than the restoration of plant–soil feedback. The lower immobilization of nutrients in microbial biomass and lower retention of nutrients in restored areas, compared with native savanna, is expected to favour the re‐establishment of fast‐growing exotic species. Synthesis and application . Despite reducing the resprouting and germination of exotic grasses and improving the establishment of native grasses in the short term, restoration practices have major impacts on the soil microbial community and soil fertility. The reduction of soil microbial biomass and organic matter content reduces the immobilization of soil nutrients and is expected to favour a fast nutrient turnover in the ecosystem. This may result in the re‐establishment of exotic grasses in the long term. Future efforts should focus on the recovery of soil organic matter content and the establishment of soil microbial communities similar to native ecosystems after the application of land‐management practices. Therefore, the restoration of abandoned pastures should consider a greater focus on restoring soil carbon and nutrient cycling Abstract : Despite reducing the resprouting and germination of exotic grasses and improving the establishment of native grasses in the short term, restoration practices have major impacts on the soil microbial community and soil fertility. The reduction of soil microbial biomass and organic matter content reduces the immobilization of soil nutrients and is expected to favour a fast nutrient turnover in the ecosystem. This may result in the re‐establishment of exotic grasses in the long term. Future efforts should focus on the recovery of soil organic matter content and the establishment of soil microbial communities similar to native ecosystems after the application of land‐management practices. Therefore, the restoration of abandoned pastures should consider a greater focus on restoring soil carbon and nutrient cycling.